Groundwater Quality Assessment for Irrigation in Madhavaram - Sivakumar, D; Govindasami, S; Raghul Raj, B; Gowdham, C; M. Ragothaman, V (International Journal of Engineering and Technology, 2018)
The study focused to assess the groundwater in Madhavaram, Chennai, Tamil Nadu, for irrigational purposes. Irrigation indices like SAR, SSP, PI and KR was determined in each groundwater sample to identify its irrigational suitability. This study further envisaged that these groundwater aquifers have low Sodium adsorption ratio and hence groundwater is fit for irrigation, while residual sodium bicarbonate and Kellyâ€™s ratio values indicated that majority of these aquifer have water of marginal to harmful quality against irrigation. The dominance pattern of cations in the studied ground water was in the order of Na > Ca > Mg > K and the sequence of anionic dominance was as follows: Cl > HCO3 > SO4. All 20 wells fall under the excellent category of SAR. SSP values of groundwater range from 49 to 71 and indicated that 15 wells are under permissible and 5 wells are under doubtful classification.Â PI value indicated that groundwater is unsuitable against irrigation.Â The KR indicated that groundwater quality in 18 wells is not fit for irrigation.Â Hence, necessary pre-treatment methodology is to be adopted for utilizing groundwater for irrigation purpose. Â